The creative habit learn it and use it for life : a practical guide - Tharp, Twyla 1941- (Simon & Schuster, 2003)
Creativity is not a gift from the gods, says Twyla Tharp, it is the product of preparation and effort, and it's within reach of everyone who wants to achieve it. Here, Tharp takes the lessons she has learned in her remarkable thirty-five-year career and shares them with you, whatever creative impulses you follow--whether you are a painter, composer, writer, director, choreographer, or, for that matter, a businessperson working on a deal, a chef developing a new dish, a mother wanting her child to see the world anew. When Tharp is at a creative dead end, she relies on a lifetime of exercises to help her get out of the rut, and The Creative Habit contains more than thirty of them to ease the fears of anyone facing a blank beginning and to open the mind to new possibilities.--From publisher description.
Keywords: Tharp, Twyla -- 1941-; Création artistique; Création littéraire; Créativité; Habitude; Creative ability; Creative thinking; Creation (Literary, artistic, etc.); Kreativität; Kunst; Literatur; Guide (Descripteur de forme)